Contemporary Developments in Islamic Law, Civil Law, Criminal Law and Administrative Law - Mohammad Zakkii; Sutrisno (Badan usaha Milik Desa Berkaho Pungpungan, 2025)
This paper explores contemporary developments in Islamic law in tandem with evolving transformations across civil, criminal, and administrative legal systems in Muslim-majority countries. As these nations navigate a complex interplay between traditional jurisprudence and the demands of modern governance, the harmonization of Islamic legal norms with constitutional law, international human rights standards, and administrative efficiency has become increasingly pertinent. The research employs a qualitative, library-based doctrinal methodology, drawing from classical texts, statutory reforms, judicial decisions, and scholarly interpretations. Countries such as Malaysia, Indonesia, Saudi Arabia, and Morocco serve as comparative models, each demonstrating unique pathways in integrating Islamic legal principles into national legal frameworks. The study reveals that the application of tools such as maqāṣid al-sharī‘ah (the higher objectives of Islamic law), ijtihād (independent reasoning), and maslahah (public interest) has enabled Islamic law to evolve without compromising its theological and moral foundations. While civil law reforms often address gender equity and personal status, criminal law reforms engage with codification and discretionary justice mechanisms. In administrative law, Islamic ethical values are increasingly embedded in governance practices, transparency norms, and anti-corruption efforts. Ultimately, the findings support the view that hybrid legal models grounded in Islamic ethics yet responsive to modern institutional frameworks represent a sustainable legal paradigm for Muslim societies in the 21st century.